Immunoproteasome impairment via β5i/LMP7‐deletion leads to sustained pancreatic injury from experimental pancreatitis. Issue 14 (15th June 2021) - de Freitas Chama, Laura L.; Ebstein, Frédéric; Wiesrecker, Birthe; Wagh, Preshit R.; Hammer, Elke; Weiss, Frank U.; Junker, Heike; Studencka‐Turski, Maja; Lerch, Markus M.; Krüger, Elke; Sendler, Matthias
Abstract: Uncovering potential new targets involved in pancreatitis may permit the development of new therapies and improvement of patient's outcome. Acute pancreatitis is a primarily sterile disease characterized by a severe systemic inflammatory response associated with extensive necrosis and a mortality rate of up to 24%. Considering that one of the reported disease mechanisms comprises the endoplasmic reticulum (ER) stress response and that the immunoproteasome is a key regulator to prevent proteotoxic stress in an inflammatory context, we investigated its role in acute pancreatitis. In this study, we demonstrate that immunoproteasome deficiency by deletion of the β5i/LMP7‐subunit leads to persistent pancreatic damage. Interestingly, immunoproteasome‐deficient mice unveil increased activity of pancreatic enzymes in the acute disease phase as well as higher secretion of Interleukin‐6 and transcript expression of the Interleukin IL‐1β, IFN‐β cytokines and the CXCL‐10 chemokine. Cell death was increased in immunoproteasome‐deficient mice, which appears to be due to the increased accumulation of ubiquitin‐protein conjugates and prolonged unfolded protein response. Accordingly, our findings suggest that the immunoproteasome plays a protective role in acute pancreatitis via its role in the clearance of damaged proteins and the balance of ER stress responses in pancreatic acini and in macrophages cytokine production.